Antifertility properties of Cissamplelos pareira Linn. leaf gel in male and female mice - Ampa Luangpirom; Thanaree Junaimuang; Pichet Somsapt (International Journal of Phytomedicine, 2015)
This study aimed to evaluate the antifertility properties of C. pareira Linn. leaf gel in male mice by evaluation of blood prolactin, testosterone and seminal quality. In females mice, estrous index, fertility index and prolactin level were determined. The results for males revealed that the leaf gel at a dose of 30 mg/100 gBW significantly increased blood prolactin, while the leaf gel at 20 and 30 mg/100 gBW decreased testosterone levels in a dose dependent manner (P<0.05). Interestingly, all doses (10, 20 and 30 mg/100 gBW) of leaf gel caused significant impairement of sperm quality collected from epididymis and vas deferens after 21 days of oral adminitration. The results for females showed that the leaf gel at 40 and 60 mg/100 gBW caused irregular estrous cycle and inhibited ovulation by decrease in estrous index during the 21 days of treatment. Meanwhile, it also revealed significant increases in blood prolactin and decreased embryo implantation in pregnant mice after 10 days of treatment. It may be concluded that C. pareira leaf gel has antifertility properties in male by disturbance of blood prolactin and testosterone levels, consequently affecting spermatogenesis and impaired sperm quality. Meanwhile, it inhibits ovulation in females and inhibits embryo implantation or decreases fertility index by increasing prolactin in pregnant mice. Therefore, the use of C. pareira leaf gel as food or for therapy in traditional medicines should be avoided because of this adverse effect.